Regularities of obtaining polymer-silicate composites from water-soluble silicates and polymers - Масюк, Андрій Сергійович; Левицький, Володимир Євстахович (Eastern-European Journal of Enterprise Technologies, 2014)
Based on the studies, the influence of nature, concentration and method of administration of polymer modifier and precipitant on physicochemical regularities of obtaining the modified polymer-silicate materials was determined. It was found that the nature and concentration of the precipitant and polymer significantly affect the output of metal-containing polymer-silicate formations. Thus, the optimum polymer concentration in the reaction medium is 0.2-0.3 mol/L. It was found that PVP dissolution should be conducted in a solution of sodium silicate solute and PVA - a metal chloride solution. This order provides the maximum polymer sedimentation degree and modification efficiency. Based on IR spectroscopic, potentiometric and sorption studies, it was found that the process of obtaining polymer-silicate material is accompanied by intermolecular interactions between the active silicate groups and functional polymer groups that promotes the uniform distribution of macromolecules in salicylic frame. The modified silicate formations are characterized by significantly lower moisture absorption value than unmodified, which is connected with the blocking of surface groups of silicate formations by PVA and PVA macromolecules and fine particle porosity reduction. The obtained metal-containing polymer-silicate materials will be characterized by high affinity for the polymer matrix when creating composites on their basis and are aimed at affecting their morphology and providing the complex with specific properties depending on the nature of the modifier and the metal cation.